An Improved Group-Based Neighbor Discovery Algorithm for Mobile Sensor Networks. (15th April 2014) - Niu, Qiang; Bao, Weiwei; Xia, Shixiong
Abstract : Wireless sensor networks have been widely used in a variety of commercial and military applications, which often require neighbor nodes to establish connection quickly. Due to high mobility of nodes, it is a challenging issue to reduce discovery delay. Most discovery designs are based on pairwise and fixed duty cycle, in which discovery is passively achieved when two nodes wake up at the same time. In order to further improve the efficiency of neighbor discovery in mobile sensor networks, this paper proposes an improved group-based neighbor discovery algorithm (IGND) which dynamically adjusts the nodes' active time based on spatial properties. This paper describes the network model and the algorithm implementation in detail. Simulation results show that the improved algorithm has a good effect in reducing discovery latency and promoting discovery efficiency.